Letters - Irvine, Francis; Irvine, Alexander (1821)
Two letters written by Francis Irvine from Sydney in 1821 and 1823, to his father Alexander Irvine of Drum, near Aberdeen. They relate to family affairs and to his problems in settling in the colony.
Manuscript reference no. : NLA MS 6308.
National Library of Australia at NLA MS 8138.
Keywords: Irvine, Francis, -- Correspondence; Irvine, Alexander -- Correspondence; New South Wales -- Social conditions -- 1788-1851.